The Analysis of the Potential of Sports Tourism in Simalungun Regency (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
Sports tourism is all kind of active and passive activities in sports or participation on informal and organized non-commercial activities and requires people to leave home or workplace. This current study aims at (1) determining the condition and status of sports tourism in Simalungun Regency; (2) analyzing the mapping of sports tourism in Simalungun Regency; and (3) analyzing the obstacles encountered in developing sports tourism in Simalungun Regency. This study applied a qualitative approach as its method. Data were collected through observation, interview, and documentation. To ensure data validity, the triangulation technique was applied then the data were analyzed by using interactive model analysis. The results of this study revealed that (1) there were some sports tourism activities existed in Simalungun, but unfortunately they had not developed yet. (2) Tigaras Village was potential to organize sports tourism event since it has Toba lake, hills, fields, and forests. (3) obstacles encountered by parties involving in tourism activities were varied but were interrelated with tourism development problems in Tigaras.